Apraxia of speech involves lesions of dorsal arcuate fasciculus and insula in patients with aphasia - Chenausky, Karen (Neurol Clin Pract, 2020)
OBJECTIVE: To determine the contributions of apraxia of speech (AOS) and anomia to conversational dysfluency. METHODS: In this observational study of 52 patients with chronic aphasia, 47 with concomitant AOS, fluency was quantified using correct information units per minute (CIUs/min) from propositional speech tasks. Videos of patients performing conversational, how-to and picture-description tasks, word and sentence repetition, and diadochokinetic tasks were used to diagnose AOS using the Apraxia of Speech Rating Scale (ASRS). Anomia was quantified by patients' scores on the 30 even-numbered items from the Boston Naming Test (BNT). RESULTS: Together, ASRS and BNT scores accounted for 51.4% of the total variance in CIUs/min; the ASRS score accounted for the majority of that variance. The BNT score was associated with lesions in the left superior temporal gyrus, left inferior frontal gyrus, and large parts of the insula. The global ASRS score was associated with lesions in the left dorsal arcuate fasciculus (AF), pre- and post-central gyri, and both banks of the central sulcus of the insula. The ASRS score for the primary distinguishing features of AOS (no overlap with features of aphasia) was associated with less AF and more insular involvement. Only ∼27% of this apraxia-specific lesion overlapped with lesions associated with the BNT score. Lesions associated with AOS had minimal overlap with the frontal aslant tract (FAT) (<1%) or the extreme capsule fiber tract (1.4%). Finally, ASRS scores correlated significantly with damage to the insula but not to the AF, extreme capsule, or FAT. CONCLUSIONS: Results are consistent with previous findings identifying lesions of the insula and AF in patients with AOS, damage to both of which may create dysfluency in patients with aphasia.